The Effectiveness Of Bridge With Leg Reach Exercise About Flexibility Stomach and Hip - Dicky Reva Apriana Sanga Dwi (Journal of Physical Education and Sport Science, 2019)
Flexibility is a movement which the muscles are flexed (lengthened) with maximum joint motion without any significant pain. In aerobic exercise, flexibility is needed for motion and to avoid the risk of injury. The flexibility or flexibility of each person is different, therefore it can be trained with the flexibility training method, namely the bridge with leg reach exercise. This study aims to determine the effect of bridge training with leg reach flexibility. This study used the pre-post test method. Sample in this study was carried out on gymnastic participants at the Kaduagung Aerobic Club (KAC). Prior to data collection, the sample was given instructions to perform the sit and reach test flexibility test instrument. After doing the bridge with leg reach exercise for 16 meetings the sample was again retrieved through the sit and reach test flexibility test. The research resultsobtained test data then carried out the pre-post test normality test and then the results of the test data paired sample T-Test. The results of the study before the sample were given treatment the average value obtained was 2 cm, while after doing the stretching exercise the bridge with leg reach for 16 meetings showed 8.1 cm. The results of the paired sample T-Test data obtained showed the pre-test and post-test results on the flexibility test, the result was the Asymp value. Sig. (2tailed) which is equal to 0,000, smaller than α = 0.05. This result is smaller than α = 0.05, so the research data is significant.